Pengembangan Herbarium Pteridophyta Yang Diperoleh Di Area Wisata Kedung Cinet Jombang Sebagai Media Pembelajaran Botani Tumbuhan Rendah - Ospa Pea Yuanita Meishanti; Fainnana Nilna Minah; Mucharommah Sartika Ami (Universitas KH. A. Wahab Hasbullah, 2018)
Kedung Cinet is a tourist area in Jombang Regency that is often visited by tourists. This tourist area is a stream that has naturally formed limestone rock walls. Continuous tourist visits can pose a risk of damage to the natural environment such as damage to the Pteridophyta plants that are widely spread on the site. Therefore, it is necessary to collect the Pteridophyta plants. The Pteridophyta plants obtained were then identified and preserved into a herbarium and stored at the KH Botanical University Laboratory. A. Wahab Hasbullah Tambakberas Jombang. Herbarium Pteridophyta in addition to collections, is used as a learning medium in the course of Low Botanical Botany. The purpose of the study was to describe the feasibility and level of attractiveness of the Pteridophyta herbarium media. This study uses the ADDIE research model. Research procedures go through 5 stages: 1) analysis 2) design 3) development 4) implementation and 5) evaluation. Media validation was carried out by two media experts while response validation was carried out by 10 Biology Education study program students. The results showed that the herbarium was declared